Association between childhood trauma and brain anatomy in women with post-traumatic stress disorder, women with borderline personality disorder, and healthy women. Issue 1 (1st January 2021) - Rosada, Catarina; Bauer, Martin; Golde, Sabrina; Metz, Sophie; Roepke, Stefan; Otte, Christian; Wolf, Oliver T.; Buss, Claudia; Wingenfeld, Katja
ABSTRACT: Background: Childhood trauma (CT) is associated with altered brain anatomy. These neuroanatomical changes might be more pronounced in individuals with a psychiatric disorder. Post-traumatic stress disorder (PTSD) and borderline personality disorder (BPD) are more prevalent in individuals with a history of CT. Objective: In this study, we examined limbic and total brain volumes in healthy women with and without a history of CT and in females with PTSD or BPD and a history of CT to see whether neuroanatomical changes are a function of psychopathology or CT. Method: In total, 128 women ( N = 70 healthy controls without CT, N = 25 healthy controls with CT, N = 14 individuals with PTSD, and N = 19 individuals with BPD) were recruited. A T1-weighted anatomical MRI was acquired from all participants for Freesurfer-based assessment of total brain, hippocampus, and amygdala volumes. Severity of CT was assessed with a clinical interview and the Childhood Trauma Questionnaire. Group differences in hippocampal and amygdala volumes (adjusted for total brain volume) and total brain volume (adjusted for height) were characterized by analysis of covariance. Results: Volume of the total brain, hippocampus, and amygdala did not differ between the four groups (p > .05). CT severity correlated negatively with total brain volume across groups ( r = −0.20; p = .029). Conclusions: CT was associated with reduced brain volume but PTSD or BPD was not. The association between CT and reduced brain volume as a global measure of brain integrity suggests a common origin for vulnerability to psychiatric disorders later in life. HIGHLIGHTS: No group differences (healthy women with and without CT, women with BPD and CT, women with PTSD and CT) in hippocampal, amygdala, and total brain volume. Significant negative association between CT severity with total brain volume and depressive symptoms with hippocampal volumes.